1994
DOI: 10.1111/j.1553-2712.1994.tb02439.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress Levels in EMS Personnel: A Longitudinal Study with Work‐schedule Modification

Abstract: Objective:To determine if stress levels of emergency medical services (EMS) personnel can be reduced by adjusting work schedules to personnel preferences. Methods:A prospective, longitudinal, cohort study with a work‐schedule modification intervention was performed. All EMS personnel employed by the City of Cleveland EMS were eligible for participation. EMS employees voluntarily completed an abbreviated medical personnel stress survey (MPSS‐R), a 20‐question validated stress‐assessment tool, in September 1989,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Cydulka et al 17 found that 89% of EMT-Paramedics reported that their job was stressful and were psychologically worn out, or exhausted. Research indicates that the emotional labor (surface acting and deep acting) involved in being an EMS professional can play a role in such exhaustion.…”
Section: The Role Of Stress In Ems Retentionmentioning
confidence: 99%
“…Cydulka et al 17 found that 89% of EMT-Paramedics reported that their job was stressful and were psychologically worn out, or exhausted. Research indicates that the emotional labor (surface acting and deep acting) involved in being an EMS professional can play a role in such exhaustion.…”
Section: The Role Of Stress In Ems Retentionmentioning
confidence: 99%
“…The majority of health outcomes, and all WLB ones, were self-reported. In a sizeable number of the CWW studies, the intervention was either at the behest of the work force,3436 41 47 49 60 69 70 83 or from the management (with a stated desire to improve health or WLB) 37 50 6264 66 71 74 79 80 82. However, in other studies, the motivation was more obviously efficiency or productivity 46 48 51 53 54 59 61 67 77 78 81.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of the CWW interventions on health outcomes were not conclusive: a number of studies reported some improvements in workforce health,34 – 38 4245 47 – 50 52 54 5660 62 – 65 67 68 72 – 74 78 – 83 whilst others found no change,39 40 46 53 55 66 69 – 71 75 76 77 and two found only negative effects 41 51…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations